IMMU-16. CHARACTERISTICS OF EGFRVIII-DIRECTED CART CELL INFUSION PRODUCT ASSOCIATED WITH CLINICAL RESPONSE IN RECURRENT GLIOBLASTOMA. (12th November 2021) - Tang, Oliver; Binder, Zev; Tian, Lifeng; Chang, Wan-Jung; Yoder, Todd; Lacey, Simon; Melenhorst, Jos; O'Rourke, Donald M
Abstract: BACKGROUND: A therapeutic approach for chimeric antigen receptor T (CART) cell therapy in glioblastoma is targeting the epidermal growth factor receptor variant III (EGFRvIII), present in approximately 30% of glioblastomas. While earlier research demonstrated that phenotypic and genotypic characteristics in patient T cells and CART product may predict therapeutic success for hematologic malignancies, no study has investigated such determinants for clinical response in glioblastoma. METHODS: We analyzed apheresis and infusion products for patients in the first-in-human trial of EGFRvIII-directed CART for recurrent glioblastoma (NCT02209376, n=9). Inherent T cell phenotypes were characterized by flow cytometry assay using a panel of 27 markers. Clinical response was quantified via engraftment in peripheral circulation and time-on-trial (ToT). RESULTS: Mean area under the curve (AUC) peripheral CART engraftment for the study period was 213 log10 copies/μg (SD=173) and mean ToT was 134 days (SD=173). For the CAR + /CD4 + population in the infusion product, PD1 positivity was positively associated with AUC engraftment (r=0.753, P =0.012) and ToT (r=0.800, P =0.010). On immune checkpoint inhibitor analysis, CTLA-4, TIM3, and LAG3 did not exhibit significant associations with AUC engraftment or ToT. For activation markers, PD1/GRZB (r=0.794, P =0.011) and PD1/HLA-DR (r=0.769, P =0.016) were directly associated with ToT. PD1/GRZB was also predictive of AUC engraftment (r=0.794, P =0.011). For the CAR + /CD8 + population, PD1 positivity correlated with elevated AUC engraftment (r=0.639, P =0.047). In the CAR - /CD4 + population, PD1 remained positively correlated with AUC engraftment (r=0.690, P =0.027) and ToT (r=0.726, P =0.027). No significant associations were observed for apheresis products. CONCLUSION: PD1 in CART infusion products predicted peripheral engraftment and ToT in recurrent glioblastoma. Double-positive cells for PD1 and activation markers also displayed a positive correlation, suggesting PD1 highlights a population of activated CAR T cells. Further characterization of predictors of EGFRvIII-directed CART treatment efficacy may improve selection of patients and starting T cell populations for clinical expansion.